Design of Decision Support System for New Employee Recruitment at PT Motekar Edukasi Indonesia Using Scrum and SMART Methods - Ranti Tika Gantika; Amelia Kurniawati; Fahmy Habib Hasanudin (School of Industrial and System Engineering, Telkom University, 2024)
Recruitment success that depends on accurate selection is the focus of PT Motekar Edukasi Indonesia, aprofessional training services company, which is experiencing challenges in determining suitablecandidates. The company's Head of HRD experiences difficulties in recommending the right employees, aswell as in making decisions to determine employees who meet the required criteria, so a system is neededfor the Head of HRD to determine the best applicants for PT Motekar Edukasi Indonesia according to thecriteria or specifications that have been determined. To overcome this, an HRD decision support systemwas developed using the Scrum method and the Simple Multi Attribute Rating Technique (SMART)method to determine the best applicants based on established criteria. This system was tested and showedhigh accuracy and user satisfaction of 93.80%, providing an effective solution for PT Motekar EdukasiIndonesia's HRD team in the recruitment process. Implementation of a decision support system in acompany improves information structure, data processing and management, effectiveness of selection,recruitment decisions, and provides secure and flexible data storage.